An Analysis of Lexicons in Costumes of Baris Gede Dance at Penuktukan Village - Luh Wulan Aprilianti (International Journal of English Education and Linguistics (IJoEEL), 2023)
This research aims to find out the lexicons and the cultural meaning in the costumes of the Baris Gede dance. Baris Gede dance is a traditional Balinese dance that tells about warriors fighting on the battlefield. Costumes are an important component in the Baris Gede dance because the costumes used represent the contents of the dance. This research used qualitative research with interviews and observation as the method to obtain the data. The researcher found 14 lexicons in the costumes; head costume (1 lexicon) that is gelungan, neck costume (1 lexicon) which is badong/bapang, hand costume (1 lexicon) which is gelang kana, upper body costume (7 lexicons) which are awiran, oncer, lamak, kwace selem, tali semayut, keris, and urangka and lower body costume (4 lexicons) that are stewel, jaler putih, kancut putih, and sabuk. The cultural meaning relates to the soldiers on the battlefield. Warriors are depicted as dashing and brave figures represented through the Baris Gede dance costume.